Erros de prescrição em unidade de terapia intensiva neonatal - Machado, Ana Paula Cezar (2014)
Introduction Pediatric patients, especially those admitted to neonatal intensive care units (NICU), are highly vulnerable to medication errors. Several studies have shown that most errors occur during the prescription. The present study aims to know the incidence of prescription errors in the Neonatal Intensive Care Unit, the susceptible patients, the types of errors, as well as the drugs involved. Methods: Retrospective study conducted in the NICU of the Clinical Hospital of the Federal University of Uberlândia. All variables related to prescribed medications were compared with the database (Neofax) used for prescription in that NICU. Results: 150 newborns with mean gestational age of 33.8 weeks participated in the study. 1491 medication items of 478 prescriptions, involving 46 drugs, were analyzed. The rate of prescription errors was 63.4%. Errors related to dose, intervals, diluents and administration rate were encountered into 7 classes of drugs. The drug classes more involved in errors were of anti-infective for systemic use and drugs that act on the nervous and cardiovascular systems. The occurrence of errors was higher in preterm infants. Conclusion: Prescription errors were common, especially in preterm infants. The most frequent errors were related to the diluents, doses and intervals. The classes of drugs most involved in errors were anti-infective agents and those that act on the nervous and cardiovascular systems.